Changes in opioid prescribing after implementation of mandatory registration and proactive reports within California's prescription drug monitoring program. (1st January 2021) - Castillo-Carniglia, Alvaro; González-Santa Cruz, Andrés; Cerdá, Magdalena; Delcher, Chris; Shev, Aaron B.; Wintemute, Garen J.; Henry, Stephen G.
Highlights: California's updated PDMP added proactive reports and mandatory registration. These features were associated with a short-term decrease in 3/7 prescribing outcomes. Decreases in quantity and risky opioids prescribing ranged between 8% and 14 %. Freqency and other high-risk opioid prescribing patterns remained unchanged. Abstract: Background: : In 2016, California updated its prescription drug monitoring program (PDMP), adding two key features: automated proactive reports to prescribers and mandatory registration for prescribers and pharmacists. The effects of these changes on prescribing patterns have not yet been examined. We aimed to evaluate the joint effect of these two PDMP features on county-level prescribing practices in California. Methods: : Using county-level quarterly data from 2012 to 2017, we estimated the absolute change associated with the implementation of these two PDMP features in seven prescribing indicators in California versus a control group comprising counties in Florida and Washington: opioid prescription rate per 1000 residents; patients' mean daily opioid dosage in milligrams of morphine equivalents[MME]; prescribers' mean daily MME prescribed; prescribers' mean number of opioid prescriptions per day; percentage of patients getting >90 MME/day; percentage of days with overlapping prescriptions for opioids and benzodiazepines; multiple opioid provider episodes per 100, 000 residents. Results: : Proactive reports and mandatory registration were associated with a 7.7 MME decrease in patients' mean daily opioid dose (95 %CI: -11.4, -2.9); a 1.8 decrease in the percentage of patients prescribed high-dose opioids (95 %CI: -2.3, -0.9); and a 6.3 MME decrease in prescribers' mean daily dose prescribed (95 %CI: -10.0, -1.3). Conclusions: : California's implementation of these two PDMP features was associated with decreases in the total quantity of opioid MMEs prescribed, and indicators of patients prescribed high-dose opioids compared to states that had PDMP's without these features. Rates of opioid prescribing and other high-risk prescribing patterns remained unchanged.